14.3k views
1 vote
Help somebody please

Help somebody please-example-1
User Pradyot
by
5.1k points

2 Answers

4 votes


answer \\ = 62 \\ solution \\ x = 3 \\ 2 {x}^(2) + 15x - 1 \\ = 2 {(3)}^(2) + 15 * 3 - 1 \\ = 2 * 9 + 45 - 1 \\ = 18 + 45 - 1 \\ = 63 - 1 \\ = 62 \\ hope \: it \: helps

User Defne
by
5.2k points
3 votes

Answer:


62

Explanation:


2x^2+15x-1


2(3)^2+15(3)-1


2(9)+15(3)-1


18+45-1


=62

User Aichingm
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.